(untitled) (Journal of Global Accounting, 2023)
The study examined the effect of debtors management on financial performance of listed pharmaceutical companies in Nigeria. The ex post facto research design was adopted. The population of the study comprised of seven (7) listed pharmaceutical companies on the Nigeria Exchange Group in 2023. The entire seven (7) listed pharmaceutical companies was chosen as the sample size using the census approach. Data was obtained from the financial report of selected listed pharmaceutical companies on the Nigerian Exchange Group for the period of 2015-2019. The data collected was analysed using the Pearson correlation coefficient and multiple regression computed with the aid of Stata12 software. The study revealed that average collection period has a significant effect on net profit margin whereas debtor turnover does not have any significant effect on net profit margin of listed pharmaceutical companies in on the Nigerian Exchange Group. The study recommended that pharmaceutical companies should reduce average collection period in order to improve their financial performance. Finally, Pharmaceutical companies should maintain their debtor turnover to have a good net profit margin.